Ioan Mihoc, Iosif Stancovici (eds.), “Fides qua per caritatem operatur: studii biblice” [“Fides qua per caritatem operatur: biblical studies”], (Iași: Doxologia, 2023), 495 p. - CIOATĂ, Maria (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2023)
This volume brings together studies which have been presented at the International Symposium of Biblical Exegesis at the West University of Timișoara in 2020 and 2021. The symposium took place with the blessings of His Beatitude Ioan Metropolitan of Banat. The publication by Doxologia in Jassy has received the blessings of His Beatitude Teofan, Metropolitan of Moldavia and Bucovina. A short preface introduces the volume and each article. Every chapter has its bibliography, instead of an overall bibliography at the end of the volume.